2021
DOI: 10.3846/btp.2021.13336
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ways of Improving Green Economy and Environmental Protection in the Context of Governance

Abstract: Today, the principles of a green economy are being updated and studied not only by experts in the field of environmental economics, but also in various political circles. A large number of countries use different instruments and principles of a green economy in their development policies and strategies. However, some countries fear this transformation because they believe that the transition to a green economy model may hinder their development. Thus, the formation of a clear methodology for the “green” econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A number of previous studies have examined various topics and problems related to the Green Economy. Pliavskyiy, revealed that several countries are worried and believe that shifting the economy towards a green economy could hamper the country's development due to differences in green economy instruments and principles for each country (Pliavskyiy et al, 2021). Research by Liu in China shows that expanding financial inclusion can contribute to increasing environmentally friendly economic capabilities (Z. .…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have examined various topics and problems related to the Green Economy. Pliavskyiy, revealed that several countries are worried and believe that shifting the economy towards a green economy could hamper the country's development due to differences in green economy instruments and principles for each country (Pliavskyiy et al, 2021). Research by Liu in China shows that expanding financial inclusion can contribute to increasing environmentally friendly economic capabilities (Z. .…”
Section: Introductionmentioning
confidence: 99%
“…Concepts of sustainable development and green growth strategies cover social, economic, and environmental issues. Natural resources and independence of the points of fossil fuels are one of the Green growth strategies (Pyliavskyi et al, 2021). Energetics is one of the leading areas where it is possible and efforts are being made to reduce the impact of climate change as strongly as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Dijagram dekompozicije unapređenja procesa zelene ekonomije u zemlji Figure 3 -Decomposition diagram of the improve the process of green economy in the countryIzvor / Source:Pyliavskyi et al, 2021 …”
mentioning
confidence: 99%